Ultrasonographic assessment of strength of previous cesarean scar during pregnancy - Jha, Neeti Nisha S.; Maheshwari, Sunita; Barala, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Management of a woman who has undergone a previous cesarean section, has always been a controversial topic, with the inability to precisely confirm the integrity of the scarred lower uterine segment (LUS) being the indication of repeat cesarean section. The objective of this study is to evaluate the accuracy of ultrasonography (USG) in determining the LUS thickness in women with previous cesarean section (CS) and to assess its usefulness in predicting the risk of uterine rupture during a trial of vaginal birth. Methods: A prospective study was conducted on 100 women between 37 to 40 weeks of gestation with a previous CS and 100 primigravidae women serving as control. Thickness of LUS was measured by transabdominal USG. The decision for mode of delivery was based purely on obstetric ground. Patients undergoing CS were considered for analysis. Results: Mean LUS thickness was higher in the control group. Seventy-one patients of control group underwent repeat CS, in which 47 (66.1%) had normal intraoperative finding. 24 (33.7%) had abnormal LUS intraoperatively (LUS thinning). Of these, 20 (28.6%) showed abnormal LUS on USG (<5mm), but 4(5.6%) had normal ultrasonographic finding. Sensitivity, specificity, positive and negative predictive value of ultrasonographic evaluation were found to be 100%, 83.3%, 92% and 100% respectively. Conclusions: Prenatal scar assessment by USG is useful in evaluation of previous cesarean scar and in most cases a near accurate evaluation was possible.